Enhancing User Experience in Smart Insole Applications: A UI/UX Approach for Effective Foot Pressure Monitoring and Gait Analysis in Plantar Fasciitis Management. (Journal of Informatics Education and Research, 2025)
Smart insole technology has emerged as a valuable tool for managing plantar fasciitis by providing real-time foot pressure monitoring and gait analysis. However, the success of these applications depends heavily on the user interface (UI) and user experience (UX) design, which directly influence user engagement, compliance, and the effectiveness of the technology. This study focuses on enhancing the UI/UX design of smart insole applications to optimize the user experience for individuals managing plantar fasciitis. By analyzing common user challenges and designing intuitive interfaces, the research aims to improve usability, data visualization, and personalized feedback in foot pressure monitoring and gait analysis. A user-centered design approach was employed to identify pain points and develop features that address the specific needs of patients with plantar fasciitis, such as customized alerts for excessive pressure and easy-to-understand data displays. The study highlights the importance of an accessible and engaging UI/UX design in ensuring adherence to treatment plans and maximizing the therapeutic benefits of smart insoles.